2021
DOI: 10.12998/wjcc.v9.i23.6798
|View full text |Cite
|
Sign up to set email alerts
|

Psoriasis treatment using minimally manipulated umbilical cord-derived mesenchymal stem cells: A case report

Abstract: BACKGROUND Psoriasis is a chronic autoimmune disease that usually manifests as a red scaly epidermis, induration, and hyperproliferation of basal keratinocytes. About 2% of the world’s population suffers from psoriasis but there are no clear therapeutics yet. Recently, mesenchymal stem cells (MSCs) have been regarded as a therapeutic alternative for autoimmune diseases, as they possess immunosuppressive effects without risks. Human umbilical cord-derived MSCs effectively regulate immune cells and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 17 publications
(22 reference statements)
0
6
0
Order By: Relevance
“…A male patient who had received various psoriasis treatments for 25 years without ideal efficacy showed significant improvement after intravenous transplantation (3.0 × 10 6 cells/mL) and local transplantation (1.0 × 10 6 cells/mL) of umbilical cord-derived MSCs transplantation. 49 And in the long follow-up of 4 to 5 years, a female patient showed no psoriatic relapse signs after three infusions and two more consolidating infusions of umbilical cord-derived MSCs (1.0 × 10 6 /kg for each time). Unexpected psoriasis relief was observed in a male patient who had suffered psoriasis for 12 years during the treatment of newly diagnosed diffuse large B-cell lymphoma (stage IV) with standard lymphoma chemotherapies and autologous hematopoietic stem cell transplantations.…”
Section: Msc Therapy In Psoriasismentioning
confidence: 93%
“…A male patient who had received various psoriasis treatments for 25 years without ideal efficacy showed significant improvement after intravenous transplantation (3.0 × 10 6 cells/mL) and local transplantation (1.0 × 10 6 cells/mL) of umbilical cord-derived MSCs transplantation. 49 And in the long follow-up of 4 to 5 years, a female patient showed no psoriatic relapse signs after three infusions and two more consolidating infusions of umbilical cord-derived MSCs (1.0 × 10 6 /kg for each time). Unexpected psoriasis relief was observed in a male patient who had suffered psoriasis for 12 years during the treatment of newly diagnosed diffuse large B-cell lymphoma (stage IV) with standard lymphoma chemotherapies and autologous hematopoietic stem cell transplantations.…”
Section: Msc Therapy In Psoriasismentioning
confidence: 93%
“…They also have low immunogenicity and have many advantages in the treatment of immune-related diseases. Reports have indicated that hUC-MSCs transplantation can treat psoriasis patients ( 4 ). hUC-MSCs are a safer psoriasis treatment option than topical glucocorticoids and can effectively avoid the adverse reactions caused by topical glucocorticoids on the epidermis.…”
Section: Discussionmentioning
confidence: 99%
“…The effects of epidermal stem cells and stem cells on T cells have been found. The dysfunction of various types of stem cells may be the main reason for the dysregulation of inflammatory response in psoriasis ( 3 , 4 ). Human umbilical cord mesenchymal stem cells (hUC-MSCs) are characterized by low immunogenicity, high expansion rate in vitro , and pluripotent differentiation potential, and they can be used as the ideal choice of mesenchymal stem cells for the treatment of psoriasis.…”
Section: Introductionmentioning
confidence: 99%
“…After both intravenous and local administration of UC-MSCs, his erythema gradually disappeared (10 ml for intravenous administration with 3 × 10 6 cells/ml in 0.9% physiological saline and 2–4 ml for local administration with 1 × 10 6 cells/ml in 0.9% physiological saline). The follow-up was 122 days, and the symptom was gradually becoming better without any side effects ( 77 ). In addition, in a 17-patient clinical trial, Cheng et al.…”
Section: The Clinical Efficacy Of Mscs and Their Derivatives Applied ...mentioning
confidence: 99%